Drug-Induced Interstitial Lung Disease From PARP Inhibitors (Olaparib and Niraparib) for Ovarian Cancer - Hiroshi Sugimoto; Takanori Enomoto; Mamoru Okuno; Naoko Chayahara; Hiroki Morita; Kyosuke Nakata (Annals of Internal Medicine: Clinical Cases)
Poly (ADP-ribose) polymerase (PARP) inhibitors are approved for the treatment of several types of cancers. We report a case of an 80-year-old Japanese woman who developed drug-induced interstitial lung disease (ILD) during treatment with PARP inhibitors (olaparib and niraparib) for ovarian cancer. Bronchoalveolar lavage revealed elevated lymphocytes and eosinophils with no pathogens or malignant cells. After treatment with prednisolone, PARP inhibitor–induced ILD improved. This patient case suggests that PARP inhibitor–induced ILD may be caused by allergic processes with cross-reactivity between PARP inhibitors. Therefore, although further studies are required, switching to another PARP inhibitor in patients with PARP inhibitor–induced ILD should be carefully considered.